The Problems and Challenges English Teachers Face in Teaching Students with Disabilities - Baharuddin, Baharuddin; Linusi, Yusril; Amin, Muhammad (Universitas Nahdlatul Wathan Mataram, 2022)
This research dealt with the analysis of teaching challenges faced by English teacher in teaching disabled students. The objectives of the research were to describe problem faced by English teachers, factors caused the problems and solutions taken to face the problems. Descriptive qualitative method was applied in conducting this study. The data were taken from the English teachers who taught English at the VIII grade at SMPLB Negeri 1 Lombok Barat, province of West Nusa Tenggara, based on the observation, documentation and interview from August 9 until September 5, 2021. It was found that the challenges faced by the teacher in teaching there are of management class, Lack of communication between teachers and students, and Lack of reading and writing skills. It was also found the factors of causing the problems such as students have intellectual disability and teacher's education background and physical. The solutions were found as using TPR method, double assistances and private assistant. Finally, this research finding could be useful for English teachers to teach English for mild intellectual disability in a better way despite the many challenges that probably appeared.